Toking their way sober: alcoholics and marijuana as folk medicine - Lenza, Michael (Contemporary justice review, 2007)
In this exploratory study, 18 semistructured life-history interviews were conducted with heavy drinkers who substituted marijuana for their alcohol use. Folk knowledge on the efficacy of marijuana in self-treatment for alcoholism, particularly associative depression and anxiety disorders, is examined. The study views the impacts of alcohol and marijuana on the subjects’ ability to sustain viable normative selves in their daily interaction orders. Other instrumental uses of marijuana, consciousness expansion and social facilitation, are also presented as well as how normative dosages of marijuana can be socially constructed and transmitted within rituals of use.